A pilot study exploring the relationship between self-compassion, self-judgement, self-kindness, compassion, professional quality of life and wellbeing among UK community nurses. (November 2016) - Durkin, Mark; Beaumont, Elaine; Hollins Martin, Caroline J.; Carson, Jerome
Abstract: Background: Compassion fatigue and burnout can impact on performance of nurses. This paper explores the relationship between self-compassion, self-judgement, self-kindness, compassion, professional quality of life, and wellbeing among community nurses. Aim: To measure associations between self-compassion, compassion fatigue, wellbeing, and burnout in community nurses. Method: Quantitative data were collected using standardised psychometric questionnaires: (1) Professional Quality of Life Scale; (2) Self-Compassion Scale; (3) short Warwick Edinburgh Mental Wellbeing Scale; (4) Compassion For Others Scale, used to measure relationships between self-compassion, compassion fatigue, wellbeing, and burnout. Participants: A cross sectional sample of registered community nurses ( n = 37) studying for a postgraduate diploma at a University in the North of England took part in this study. Results: Results show that community nurses who score high on measures of self-compassion and wellbeing, also report less burnout. Greater compassion satisfaction was also positively associated with compassion for others, and wellbeing, whilst also being negatively correlated with burnout. Conclusion: High levels of self-compassion were linked with lower levels of burnout. Furthermore when community nurses have greater compassion satisfaction they also report more compassion for others, increased wellbeing, and less burnout. The implications of this are discussed alongside suggestions for the promotion of greater compassion. Highlights: Self-compassion was significantly associated with less burnout and in community nurses. Compassion satisfaction correlated positively and significantly with wellbeing, compassion for others, and less burnout. =Community nurses scored high (M = 4.1) on measures of compassion for others in relation to psychology students in the USA. Research is needed to explore how self-compassion and self-judgement effect burnout, compassion fatigue and compassion.